IMPLEMENTASI RENCANA PEMBELAJARAN MENDALAM (RPM) UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG BENCANA ALAM BANJIR AKIBAT AKTIVITAS MANUSIA - Rachma Anandita, Adinda; Fadhillah, Dilla; Nur Safitri, Rahma; Rahmawati, Siti; Az Zahra, Zaen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of implementing the Deep Learning Lesson Plan (Rencana Pembelajaran Mendalam/RPM) in improving students’ understanding of flood disasters caused by human activities. The research employed a quantitative method using a pre-experimental One Group Pretest–Posttest design involving 30 students. The research instruments consisted of 10 multiple-choice questions administered as pretests and posttests. Data were analyzed using a paired sample t-test with the assistance of SPSS. The results showed that the average pretest score was 4.23, while the posttest score increased to 7.87, with a significance value of 0.000 (p < 0.05), indicating a significant improvement in students’ understanding after the implementation of RPM. Therefore, the implementation of RPM is effective in enhancing students’ understanding of flood disaster material.